Efektifitas Media Model dalam Meningkatkan Kemampuan Memasang Pakaian Dalam Pada Anak Tunagrahita Sedang Kelas X C1 di SLB Wacana Asih Padang (Single Subject Research) - TIFANI HERDIANI (Jurnal Penelitian Pendidikan Khusus, 2015)
AbstractThis research was conducted based on a problem found at SLB Wacana Asih Padang indicating that a student with medium mental retardation in class X C1 got difficulties to wear underwear. Therefore, this research was aimed at revealing the effectiveness of modeling media to enhance the ability of the student with medium mental retardation to wear underwear in class X C1 of SLB Wacana Asih Padang.This was an experimental research which applied Single Subject Research (SSR) and A-B-A design. The data gathered in this research were analyzed by using visual analysis of graphic. The subject of the research was a student with medium mental retardation in class X C1. Through this research, the student was required to do sixteen activities of wearing underwear. The assessment in this research was done by using percentage technique.In the baseline condition (A1) that consisted of six meetings, the mean level was 39,6 and the tendency of direction improved (+), in intervention condition (B) that consisted of seven meeting, the mean level was 78,2 and the tendency of direction improved (B), and in the baseline condition (A2) that consisted of six meetings the mean level was 91,5 and the tendency of direction also improved (+). The percentage of the data overlapped between the baseline condition (1) and the intervention condition (B) was 0%, and between the baseline condition (A2) and the intervention (B) was 14,28%. These results indicated that the smaller the percentage of the data overlapped, the better the effect of the intervention. Based on these results, it was concluded that the use of modeling media was effective to enhance the skill of the student with medium retardation to wear underwear in class X C1 of SLB Wacana Asih Padang. Kata Kunci: media model; meningkatkan kemampuan; memasang pakaian dalam; tunagrahita sedang